Effect of intensified emission during the generation of a submillisecond low-energy electron beam in a plasma-cathode diode; IEEE Transactions on Plasma Science; Vol. 37, iss. 10 - Koval N. N. Nikolay Nikolaevich; Grigoryev S. V.; Devyatkov V. N.; Teresov A. D.; Schanin P. M. (2009, 2009)
Title screen